PEMBUATAN RAGI DENGAN MENGGUNAKAN BEBERAPA MACAM TEPUNG SEBAGAI PEMBAWA(CARRIER) - ELIDAR ELIDAR (BERITA BIOLOGI, 1987)
ELIDAR.1987.The preparation of inoculum by using various flour as subtrates or carriers Suppl. Berita Biologi. 3: 51:55. for 2 mold and 2 yest strains,the rice,glutinous rice and tapioca wates flour colud be used as a substrate better then others flour.The survival of the inoculated microorganisms in the rice,glutinous rice and tapioca waste inoculums were not significantly difference.The viable spore count in those three inoculums decreased due to th duration of storage The viability of the spores count were  104- 106 propagule/g in the early storage and then it descreased 104 propagule/g after 3 months storage